CURA Reporter [September 1995] - University of Minnesota: Center for Urban and Regional Affairs (University of Minnesota, 1995)
This issue contains the following feature articles: Income and Poverty in Minnesota. , by Craig, William J. and John Tichy.; Treatment for African American Men Who Batter. , by Williams, Oliver J.; Accepting the Circle of Life: Lessons from the Anishinabe about Caring for Elders. , by Boss, Pauline, Lori Kaplan, and Michele Gordon.